An Analysis on the Ways Brands Are Featured in Celebrity Posts on Instagram and the Level of Sponsorship Disclosure - A. Mücahid Zengin; Güldane Zengin (Selçuk İletişim)
Brands are partnering with celebrities in both traditional and new media. Instagram is one of the widely used social media platforms where brands are trying to reach their target audiences. Celebrities are using this platform not only to connect with their fans, but also partner with brands. This study examines the posts made by Turkish celebrities on Instagram and aims to reveal the ways brands are featured in these posts. In addition, this study aims to reveal the level of sponsorship disclosure on these posts. 354 posts of 36 celebrities were found to include a visible or audible brand name, logo, slogan or an identifiable product and product package. Most prominent way of featuring a brand in a post was found to be “@mention” with 62,7%. It was also found that in 66,9% of the posts, celebrity was pictured with the brand. Out of the 354 branded posts made by celebrities, only 3,7% found to be including a sponsorship disclosure although regulations prohibit covert advertising and stipulates disclosure of product placement.